Socioeconomic Disparities and Dementia in China - Luo, Yanan; Guo, Shuai; Wang, Yiran; Pang, Lihua; Guo, Chao; Zheng, Xiaoying (Psychiatry Research, 2022)
Objectives This study aimed to investigate the associations between individual-level SES, area-level SES, and their interaction with dementia in China. Methods This study used data from the Second China National Sample Survey on Disability and restricted our finalized analysis to 688,507 participants aged 50 years or older. Dementia was ascertained according to the International Statistical Classification of Diseases, Tenth Revision. Multilevel logistic regression models were fitted to examine the associations between individual-level SES, area-level SES, and their interaction with dementia. Results Participants with higher individual SES were less likely to develop dementia; the risk of dementia decreased by 18% for each standard deviation increase in individual SES (OR=0.82, 95% CI=0.77, 0.88). Advantaged areas were associated with an increased risk of dementia in Chinese adults by 1.52 (95% CI=1.43, 1.62). Analysis of the combination between individual-level SES and area-level SES revealed that as the level of area SES increased, the risk of dementia in lower SES people was significantly higher than in higher SES people (OR=1.09, 95% CI=1.04,1.14). Discussion This study found that people with lower SES living in high-SES areas had a higher risk of dementia than people with lower SES living in low-SES areas. Significant socioeconomic differences in the risk of dementia exist in China, and more attention should be given to low-SES populations living in high-SES areas.